An Analysis of the Relationship between Nominal Exchange Rates and Stock Prices - Wu, Lina (2015)
In this dissertation, the relation between nominal exchange rates and stock prices is examined in the nine markets of Australia, Canada, Hong Kong (HK), Japan, United Kingdom (UK), Sweden, India, the Philippines and Thailand. Monthly closing observations from July 1997 to July 2015 for Thailand and from June 1995 to June 2015 for the remaining markets are used to study the interaction between the two variables. First, the results of unit root tests indicate that two variables are not stationary and integrated of order one, that is I(1). Next, no evidence of a long-term cointegration relation between the two series is discovered when Johansen’s cointegration test is employed. Then, Granger causality test shows a unidirectional Granger causality running from stock prices to exchange rates for Canada, causality in the opposite direction for Japan, UK and the Philippines, bi-direction causality between the two variables for Thailand and no any causal relationship for the remaining markets. Finally, analysis of impulse response functions reveals that data from are in agreement with the traditional approach. Increasing differenced exchange rate has a negative effect on stock return for most of markets over the sample period, and vice versa. The results of variance decompositions indicate that stock price is driven to a lesser extent by change in exchange rate for all markets while exchange rate is driven to some extent by a shock to stock return for all markets except for Sweden, HK and UK. Moreover, these findings have implications for policy makers, market researchers and global investors.